Kinetic analysis and modelling of enzymatic (R)-phenylacetylcarbinol batch biotransformation process - Leksawasdi N. (2014)
Initial rate and biotransformation studies were applied to refine and validate a mathematical model for enzymatic (R)-phenylacetylcarbinol (PAC) production from pyruvate and benzaldehyde using Candida utilis pyruvate decarboxylase (PDC). The rate of PAC formation was directly proportional to the enzyme activity level up to 5.0 U ml-1 carboligase. Michaelis-Menten kinetics were determined for the effect of pyruvate concentration on the reaction rate. The effect of benzaldehyde followed the sigmoidal shape of the Monod-Wyman-Changeux (MWC) model. The biotransformation model, which also included a term for PDC inactivation by benzaldehyde, was used to determine the overall rate constants for the formation of PAC, acetaldehyde, and acetoin. These values were determined from data for three batch biotransformations performed over a range of initial concentrations (viz. 50-150 mM benzaldehyde, 60-180 mM pyruvate, 1.1-3.4 U ml-1 enzyme activity). The finalised model was then used to predict a batch biotransformation profile at 120/100 mM initial pyruvate/benzaldehyde (initial enzyme activity 3.0 U ml-1). The simulated kinetics gave acceptable fitting (R2=0.9963) to the time courses of these latter experimental data for substrates pyruvate and benzaldehyde, product PAC, by-products acetaldehyde and acetoin, as well as enzyme activity level. © 2004 Elsevier B.V. All rights reserved.